2020
DOI: 10.1093/jscr/rjaa207
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intraneural hematoma of the common fibular nerve due to oral anticoagulation

Abstract: Compression syndromes affecting the common fibular nerve are common and frequently caused by direct pressure upon the fibular tip region. Here, we describe a case of a 50-year-old male presenting with sudden foot drop, which had developed spontaneously. He was on oral anticoagulants due to hereditary thrombophilia (factor-V-Leiden). Neurophysiology examination revealed a common peroneal nerve lesion at the fibular tip. T1-weighted magnetic resonance imaging (MRI) showed a not further classifiable hyperintensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There are some case reports without surgical excision of intraneural hematoma. Schwab et al 15 reported surgical exploration of intraneural hematoma without evacuation, due to diffuse spreading of hematoma with no relevant thickening of nerve. However, in most of intraneural hematoma, surgical evacuation was performed with good neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are some case reports without surgical excision of intraneural hematoma. Schwab et al 15 reported surgical exploration of intraneural hematoma without evacuation, due to diffuse spreading of hematoma with no relevant thickening of nerve. However, in most of intraneural hematoma, surgical evacuation was performed with good neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The scenario has been reported previously for different nerves due to either traumatic/ iatrogenic events (e.g., nerve injections) or in patients with underlying coagulopathy and antiplateletanticoagulant therapies. [1][2][3] The intraneural hemorrhage may be responsible for excessive pressure inside the epifascicular epineurium covering the sciatic nerve. Intra-neural high pressure leads to fascicular compression and progressive axonal injury diagnosed with electrodiagnostic tests.…”
mentioning
confidence: 99%